Entrepreneurial challenges of Muslim women in Malaysian SMEs - Azmi, I.A.G.; Basir, S.A.; Che Hashim, R.; Mohamed, H.A. (2014)
This paper tries to study the challenges faced by the Muslim women entrepreneurs in Malaysian SMEs. At present, only 15.9% of businesses are owned by them. This is far way behind of what has the Government of Malaysia targeted in 2011 that is 30%. The finalized questionnaires were distributed by post to 250 Muslim women entrepreneurs in Malaysian SMEs by using simple random sampling technique. The response rate is 44% which is good. It is found out that the most frequent types of challenges faced by the respondents are lack of finance (79.2%), lack of demand (50.9%) and location problem (50.9%). Meanwhile, their proposed solutions to the challenges are a mix of observing their religion (to give tithe and alms, to do recommendatory prayers and to hire orphans), doing business (to have good relationship with customers, businesswomen organizations, suppliers, competitors and workers, to obtain more information on business development and personal (to apply work life balance).